Physiological responses and tolerance mechanisms of seashore paspalum and centipedegrass exposed to osmotic and iso-osmotic salt stresses - Katuwal, Krishna B (Journal of plant physiology, 2020)
Copyright © 2020 Elsevier GmbH. All rights reserved.